Posttraumatic Displacement Management: Lateral Luxation and Alveolar Bone Fracture in Young Permanent Teeth with 5 Years of Follow-Up - Heitor Marques Honório; Catarina Ribeiro Barros de Alencar; Edmer Silvestre Pereira Júnior; Daniela Silva Barroso de Oliveira; Gabriela Cristina de Oliveira; Daniela Rios (Case Reports in Dentistry)
Dental trauma is an important public health problem due to high prevalence and associated limitations. The external impact accounting for trauma may result in different injury types to teeth and supporting structures. This paper describes a clinical case of tooth trauma in an 8-year-old patient exhibiting the displacement of three permanent teeth with open root apexes. Although the traumatic impact resulted in two injury types to teeth and supporting tissues (lateral luxation and alveolar bone fracture), the therapeutic approach was the same in both situations. The bone and teeth were repositioned by digital pressure, stabilized by semirigid splint, and followed up at every week. After six weeks, the splint was removed. At that moment, the clinical and radiographic findings indicated normal soft/hard tissues and absence of pulp/periodontal pathologies. At the fifth year of follow-up, the treatment success of the case was confirmed, although it has been observed that all lower incisors exhibited pulp obliteration as a consequence of the dental trauma.